(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In this article, the essence and modern forms of the marketing concept in the production enterprise are researched, the current state of the furniture production industry and the activity of the marketing service are analyzed, the marketing activity is analyzed, its special aspects are revealed, and proposals are made for the formation of marketing services. output is considered.